Deep neck space infections among patients attending a tertiary Ugandan hospital: clinical presentation, bacterial etiology and antimicrobial susceptibility - Nabawanga, Stella; Hidour, Rym; Kajumbula, Henry; Namwagala, Justine; Matsiko, Sedrack; Muhereza, Brian; Tumuhimbise, Michael (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Deep neck space infection (DNSI) is inflammation often with abscess collection within the potential fascial spaces in the head and neck region. There is limited data on this disease in Uganda. This study sought to determine the clinical presentation and bacterial etiology with antimicrobial susceptibility of bacterial pathogens causing DNSIs among patients at a tertiary hospital. Methods: A cross-sectional study design was used. The study population comprised 66 patients of all age groups with DNSIs. An interviewer-administered questionnaire was filled. A pus sample was taken off for culture and sensitivity. Data was entered using Epidata, validated and transferred to Stata version 16 for analysis. Results: The majority of patients with DNSI were males (59.1%) with a mean age of 21.6 years. Neck swelling (100%) and pain (95.5%) were the most common presentation. The study participants were divided into two major groups; 29 patients belonged to the pediatric group, while 37 patients belonged to the adult group. Odontogenic sources were the most common predisposing factor in the adult group and nonodontogenic sources for the pediatric group. In both groups, the submandibular space (48.4%) was the most common site of presentation. Staphylococcus aureus (34.5%) was the most common isolated organism in the pediatric group, and MRSA were 46.1% overall Viridans streptococci (37.8%) was most common in the adult group with no resistance to clindamycin. Conclusions: Susceptibility pattern varied, and highlights the necessity of doing antimicrobial sensitivity for all patients.